The modernist exoskeleton insects, war, literary form - Murray, Rachel 1989- (Edinburgh critical studies in modernist culture, 2020)
Focusing on the writing of Wyndham Lewis, D. H. Lawrence, H.D. and Samuel Beckett, this book uncovers a shared fascination with the aesthetic possibilities of the insect body - its adaptive powers, distinct stages of growth and swarming formations